Antimicrobial resistance pattern and phenotypic detection of extended spectrum beta lactamase- and Metallo beta lactamase- producing Pseudomonas aeruginosa isolated from indoor-patients suffering ear discharge: DOI: 10.48129/kjs.10773 - Ali, Farooq; Shakeela, Qismat; Uzma, Bibi; Bibi, Asma; Najeeb, Bushra; Rahman, Atta ur; Shah, Mubassir; Ahmed, Shehzad (Kuwait Journal of Science, 2022)
A multidrug-resistant bacterium due to its intrinsic resistance nature and beta-lactamases production, Pseudomonas aeruginosa (P. aeruginosa) can colonize ubiquitously and is thus associated with life-threating bacterial infections. The study was aimed to inspect phenotypic detection and antimicrobial resistance pattern of ESBL- and MBL-producing P. aeruginosa strains. 220 clinical specimens were collected from indoor patients with ear discharge were inoculated on suitable culture media. Antimicrobial resistance pattern of all isolates was investigated employing Kerby-Bauer disc diffusion method. Double-disc synergy test and Imipenem-EDTA test were used respectively to detect ESBL- and MBL-producing strains. From 220, 37 (16.82%) clinical specimens confirmed the growth of P. aeruginosa. In comparison to female (43.24%), male population (56.76%) was more prevalent. Out of 37 positive cases, 16 (43.24%) strains were detected as ESBL-producers, while 7 (18.92%) as MBL producers. Cefotaxime (100%) was found the most resisted antibiotic by isolates, followed by aztreonam (91.89%), gentamycin (86.49%), ceftriaxone (83.78%) and tazobactam/piperacillin (64.87%), while the lowest resistance was observed against imipenem (21.63%) and meropenem (51.36%). Furthermore, ESBL-producing strains revealed high resistance against cefotaxime (100%), ceftriaxone (93.75%), and carbenicillin (87.5%), while MBL-producing strains were completely resistance to imipenem, meropenem, cefotaxime and carbenicillin, followed by gentamicin (85.71%) and amikacin (75.42%). Our study concluded that strains of P. aeruginosa producing ESBL and MBL enzymes were mostly resistant to the drugs of choice, which puzzle the physicians to treat infections caused by P. aeruginosa. So, it is needed to study the resistant pattern of P. aeruginosa in order to recommend proper medication.